Engine Combustion Efficiency and Performance of Exhaust Pipe Fuel Preheating System - Budiprasojo, Azamataufiq; Irawan, Andik (Jurnal Rekayasa Mesin, 2018)
The Exhaust Pipe Preheated Fuel System (EP2FS) is a fuel preheating system that utilizes wasted heat from the muffler. Fuel heating aims to improve the homogeneity of fuel and air mixtures to improve the combustion process in the engine. Making EP2FS requires careful design and calculation because the fuel temperature should not exceed 60oC so as not to evaporate. Design and calculation, using heat transfer theory of helical heat exchanger. A ready-made system will be applied in motor vehicles to be tested for combustion efficiency and performance.